Thabo Mbeki - Adebajo, Adekeye, 1966- (Book collections on Project MUSE., 2017)
Former South African president Thabo Mbeki is a complex figure. He was a committed young Marxist who, while in power, embraced conservative economic policies and protected white corporate interests; a rational and dispassionate thinker who was particularly sensitive to criticism and dissent; and a champion of African self-reliance who relied excessively on foreign capital. As a key liberation leader in exile, he was instrumental in the ANC's antiapartheid struggle. Later, he helped build one of the world's most respected constitutional democracies. As president, though, he was unable to overcome inherited socioeconomic challenges, and his disastrous AIDS policies will remain a major blotch on his legacy. Mbeki is the most important African political figure of his generation. He will be remembered as a foreign policy president for his peacemaking efforts and his role in building continental institutions, not least of which was the African Union. In this concise biography, ideally suited for the classroom, Adekeye Adebajo seeks to illuminate Mbeki's contradictions and situate him in a pan-African pantheon.